A scale to measure perceived respiratory effort in dogs: the DeChant scale - Mallory T. DeChant; Alexandra Moesta; Nathaniel J. Hall (Frontiers in Veterinary Science)
The perceived respiratory effort (PRE) scale is a categorical psychophysical scale originally developed by Gunnar Borg and modified for numerous applications. We here propose a modification of the PRE scale with a 0–10 categorical scale for dogs, called the DeChant scale. A total of seventy-nine Labrador Retrievers were scored by video using the developed scale pre and post one of two different sprint exercise paradigms. The first exercise paradigm was 200 m in length and the second exercise paradigm was 1,200 m in length. PRE was reliably scored with an interclass correlation exceeding 0.8 for both exercise paradigms. The scale was further validated with moderate (r > 0.5) to strong correlations (r > 0.7) with core body temperature, rectal temperature, heart rate and respiration rate. The results suggest this PRE scale may be a useful, rapid and reliable visual measure of canine effort under exercise. Future research is needed for validation to other dog breeds and for use as a measure to predict detection performance or heat injury risk.